A stapled POL κ peptide targets REV1 to inhibit mutagenic translesion synthesis. (1st July 2020) - Chatterjee, Nimrat; D'Souza, Sanjay; Shabab, Mohammad; Harris, Cynthia A.; Hilinski, Gerard J.; Verdine, Gregory L.; Walker, Graham C.
Abstract: Stapled α‐helical RIR (Rev1‐interacting region) peptides of DNA POL κ bind more effectively to the RIR‐interface of the C‐terminal recruitment domain of the translesion synthesis DNA polymerase Rev1 than unstapled peptide. The tightest‐binding stapled peptide translocates into cells and enhances the cytotoxicity of DNA damaging agents while reducing mutagenesis. Drugs with these characteristics could potentially serve as adjuvants to improve chemotherapy and reduce acquired resistance by inhibiting Rev1‐dependent mutagenic translesion synthesis.